Evaluasi Ruang Terbuka Hijau Terhadap Pertumbuhan Penduduk Berbasis Spasial Di Kota Bengkulu: Evaluasi Ruang Terbuka Hijau Terhadap Pertumbuhan Penduduk Berbasis Spasial Di Kota Bengkulu - rizki fauzi; Yurike Yurike; M Faiz Barchia (Naturalis: Jurnal Penelitian Pengelolaan Sumberdaya Alam dan Lingkungan, 2026)
Green Open Space (GOS) plays a vital role in maintaining the environmental quality of urban areas. However, its availability in many Indonesian cities, including Bengkulu City, remains limited. This study aims to evaluate the condition and spatial distribution of GOS in Bengkulu City, analyze its adequacy relative to population growth, and predict future GOS needs. The methodology involved collecting primary data through field observations to assess the actual condition of GOS and secondary data from administrative maps of Bengkulu City and demographic statistics. Data analysis included GOS mapping, area calculation, identification of active parks, ground checking, and estimation of GOS requirements based on population size.The results show that in 2025, the total GOS area in Bengkulu City is 2,016.44 hectares, distributed across nine districts. Kampung Melayu District has the largest GOS area (671.30 ha), while Teluk Segara District has the smallest (7.29 ha). Of the 503 urban parks, only approximately nine function as active GOS with supporting facilities. The adequacy analysis indicates that several districts, such as Selebar, Kampung Melayu, Gading Cempaka, Singaran Pati, Sungai Serut, and Muara Bangka Hulu, meet the GOS standard relative to their population, while Ratu Agung, Ratu Samban, and Teluk Segara do not. The projection of GOS needs shows an increasing trend in line with population growth and government policies requiring green space in new residential developments.In conclusion, although some areas meet the standard, continuous monitoring and strategic GOS development are necessary to ensure adequate green space availability in the future. .